Lung Resection in Children with Necrotizing Pneumonia: Outcome and Follow-up - Frybova, Barbora; Koucky, Vaclav; Pohunek, Petr; Cejnarova, Kristyna; Coufal, Stepan; Kokesova, Alena; Dotlacil, Vojtech; Petrasova, Natalia; Pos, Lucie; Snajdauf, Jiri; Hlava, Stepan; Polivka, Natali; et al. (European journal of pediatric surgery, 2022)
INTRODUCTION: The number of patients with necrotizing pneumonia has increased in recent years. The aim of this study is to review the incidence, management, and outcome of pediatric necrotizing pneumonia requiring surgical therapy and to prove that lung resection results in favorable development of patients. We hypothesize that overall lung function in children after lung resection does not differ from that of the healthy population. MATERIALS AND METHODS: A retrospective tertiary referral center study with a prospective follow-up spirometric study of patients with necrotizing pneumonia managed between January 2010 and December 2019 was performed. RESULTS: The study cohort consisted of 1,295 patients admitted to the pediatric department for community-acquired pneumonia; 47 patients developed necrotizing pneumonia, 36 of whom underwent parenchymal lung resection. A 5-year rise in the occurrence of necrotizing pneumonia requiring resection was 77%, with a significant increase in the last 3 years (p < 0.05). The median age at the time of surgery was 32.5 (interquartile range [IQR]: 32.25) months. Streptococcus pneumoniae was the most prevalent pathogen (83%), although 53.3% of these patients were vaccinated against the agent. In 67% of patients, preresection procedures were performed: drainage of pneumothorax (17%), drainage of empyema (46%), drainage of empyema with use of alteplase (25%), and thoracoscopic decortication (12%). Surgical procedures included lobectomy (72.2%), wedge resection (13.9%), bilobectomy (8.3%), and pneumonectomy (5.6%). The postoperative complication was bronchopleural fistula in three patients. There were two (5.5%) postoperative deaths due to multiple organ failure. The follow-up spirometry was performed 43.3 (median, IQR 23.8-66.7) months after surgical intervention. Normal lung function was detected in 35 (64.8%) patients, restrictive pattern in 6 (11.1%) patients, obstructive pattern in 11 (20.4%) patients, and combined in 2 (3.7%) patients. CONCLUSION: The number of patients with necrotizing pneumonia requiring resection has increased significantly in the last 3 years (p < 0.05). Aggressive surgical treatment results in significant clinical improvement in most cases and favorable lung function outcome. Long-term follow-up showed normal spirometry in 64.8% of cases.
Keywords: počítačová rentgenová tomografie; Pneumonectomy; Humans; Pneumonia, Necrotizing; dítě; Child; následné studie; Lung; výsledek terapie; lidé; plíce; nekrotizující pneumonie; pneumektomie; Empyema; předškolní dítě; empyém; Retrospective Studies; Tomography, X-Ray Computed; Treatment Outcome; retrospektivní studie; prospektivní studie; Child, Preschool; Follow-Up Studies; Prospective Studies